Effect of Return On Asset, Capital Intensity Ratio and Firm Size on Tax Avoidance - Oktavima Wisdaningrum (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
This research aims to analyze the effect of return on asset, capital intensity ratio, and firm size on tax avoidance. The sample of this research are 17 property and real estate companies which listed in Indonesian Stock Exchange period 2016-2019. The method which used in this research is purposive sampling and multiple linear regression analysis to analyze data and supported by SPSS version 22. The result of this research show simultaneously the return on asset, capital intensity ratio, and firm size on tax avoidance with a sig. value 0,024 < 0,005 and Fcount 3,365 > Ftable 2,76 . While partially show the return on asset has influence on tax avoidance tcount 3,100 > ttable 2,00100. Capital intesity ratio and firm size has not influence on tax avoidance tcount < ttable 2,00100. For the result of coefficient determination testing (R2) show the value 0,103, which mean that 10,3% has influence by independent variable and the rest influenced by another factors